The problems facing the agricultural sector in Nigeria and the prospect of Muzara'ah and supply chain model. Issue 1 (9th February 2015) - Oladokun, Nafiu Olaniyi; Larbani, Moussa; Mohammed, Mustafa Omar
Abstract : Purpose: – The purpose of this paper is to develop a Muzara'ah–supply chain model for the purpose of enhancing agricultural financing and productivity in Nigeria. Design/methodology/approach: – In this paper, an expert survey approach was employed to validate the newly developed model. Findings: – A survey result on the model reveals that majority of the respondents agreed with the Muzara'ah–supply chain model and preferred it to the existing models. Research limitations/implications: – The main limitation of this study is limited number of respondents. Practical implications: – With this newly developed financing model that is based risk sharing principles, the application of this model could help to reduce moral hazard and enhance agricultural productivity. Originality/value: – To the best knowledge of the researchers, such kind of study for financing agriculture does not exists in the case of Nigeria.